Principales plagas en el cultivo de aguacate (Persea americana), en la zona de Mira, cantón Mira, provincia de Carchi - Palma Carrera, Christian Santiago (2023)
The Ecuadorian avocado has achieved notoriety in international markets, thereby becoming the so-called green gold for farmers. In Ecuador there are several types of avocados, the most consumed nationally are the Fuerte or Guatemalan avocado, characteristic of the Ecuadorian highland area, of medium size and dark green color with smooth skin; and Hass avocado, mostly planted for export, small in size and black in color with rough skin. The purpose of this research work was to identify the main pests in the cultivation of avocado (Persea Americana), in the Mira area, Mira canton, Carchi province, in order to carry out adequate and timely control, which reduces the damage rate in the crop, improving production results and profitability for the producer. Among the most harmful pests are thrips, which are insects that cause damage to small fruits and the leaf roller, which causes the new leaves to curl and dry out, thus causing a burn to the new shoots. Regarding its quality, producers are recommended to carry out chemical controls based on Abamectin for thrips and Cyromazine for leafrollers, also with the help of thinning pruning, since these practices would reduce the presence of pests and improve management in area.